Developing a Framework for Designing and Deploying Technology-Assisted Rehabilitation After Stroke: A Qualitative Study. (August 2021) - Jayasree-Krishnan, Veena; Ghosh, Shramana; Palumbo, Anna; Kapila, Vikram; Raghavan, Preeti
Abstract : Objective: Many unmet rehabilitation needs of patients with stroke can be addressed effectively using technology. However, technological solutions have not yet been seamlessly incorporated into clinical care. The purpose of this pilot study was to examine how to bridge the gaps between the recovery process, technology, and clinical practice to impact stroke rehabilitation meaningfully. Design: Semistructured interviews were performed using a grounded theory approach with purposive sampling of 17 diverse expert providers in acute care, inpatient, and outpatient stroke rehabilitation settings. Common themes were identified from qualitative analyses of the transcribed conversations to develop a guiding framework from the emerging concepts. Results: Four core themes emerged that addressed major barriers in stroke rehabilitation and technology-assisted solutions to overcome these barriers: (1) accessibility to quality rehabilitation, (2) adaptability to patient differences, (3) accountability or compliance with rehabilitation, and (4) engagement with rehabilitation. Conclusions: The results suggest a four-pronged framework, the A3E framework that stands for Accessibility, Adaptability, Accountability, and Engagement, to comprehensively address existing barriers in providing rehabilitation services. This framework can guide technology developers and clinicians in designing and deploying technology-assisted rehabilitation solutions for poststroke rehabilitation, particularly using telerehabilitation. Abstract : Supplemental digital content is available in the text.